Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1111/j.1750-3841.2011.02090.x
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, Nutritional, and Antimicrobial Properties of Wine Grape (cv. Merlot) Pomace Extract‐Based Films

Abstract: WGP extract-based edible films with the addition of a small amount of commercial polysaccharides showed attractive color and comparable mechanical and water barrier properties to other edible films. The films also demonstrated their potential antioxidant and antimicrobial functions. Hence, they may be used as colorful wraps or coatings for food, pharmaceutical, or other similar applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 43 publications
(65 reference statements)
2
40
0
Order By: Relevance
“…Grape marc and grape seed extract-based films have been reported to show activity against bacteria (Corrales et al 2009; Deng and Zhao 2011;Anastasiadi et al 2009;Kajiya et al 2004). In addition in previous studies, seed and skin extracts from grape winery by-products have been shown to have antibacterial and antifungal activity highlighting their potential to be used as anti-microbiological agents (Serra et al 2008).…”
Section: Bacteriamentioning
confidence: 99%
“…Grape marc and grape seed extract-based films have been reported to show activity against bacteria (Corrales et al 2009; Deng and Zhao 2011;Anastasiadi et al 2009;Kajiya et al 2004). In addition in previous studies, seed and skin extracts from grape winery by-products have been shown to have antibacterial and antifungal activity highlighting their potential to be used as anti-microbiological agents (Serra et al 2008).…”
Section: Bacteriamentioning
confidence: 99%
“…Green tea, cranberry, and cocoa are considered the most promising plant sources [8,9,10,11]. Many investigations showed that grapes and related products (grape juice and wine) resulted in exerting antibacterial activity against a wide range of bacteria because of the high content of polyphenols [12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…There are increased interests in converting this cheap biowaste into value‐added products, such as extraction of bioactive compounds as dietary supplements and grape seeds oil for promoting human health (González‐Paramás and others 2003; Maier and others 2009). Our previous studies investigated the feasibility of creating edible films using WGP extracts by utilizing the residual pectin, cellulose and sugars (Deng and Zhao 2011), and developed WGP biocomposite boards based on the thermoplastic properties of pectin, proteins, organic acids, and sugar in WGP (Park and others 2010). In addition, the chemical composition of polyphenols and dietary fiber in red and white WGP from the U.S. Pacific Northwest were characterized (Deng and others 2011).…”
Section: Introductionmentioning
confidence: 99%